A Cross-Sectional Qualitative Study of Barriers to Effective Therapeutic Communication among Nurses and Patients. Issue 6 (26th April 2021) - Arkorful, Vincent Ekow; Hammond, Anastasia; Basiru, Ibrahim; Boateng, Jennifer; Doku, Francis; Pokuaah, Sarah; Agyei, Eric Kwadwo; Baoteng, Joyce Asamoah; Lugu, Benjamin Kweku
ABSTRACT: Effective communication between patients and nurses is cardinal to health care The study seeks to explore barriers to effective therapeutic communication between patients and nurses in randomly selected health facilities in the Kumasi metropolis, Ashanti region, Ghana. The study employed an exploratory study to interview 60 respondents comprising 30 nurses and patients each, using an unstructured interview guide. In addition to nurses' and patients'perceived barriers, the study revealed the health environment–related barriers. Patients-related barriers include individual sociodemographic attributes, patient–nurse relationship, erroneous impression, and language barrier. Other identified nurses-related barriers include human resource challenges, patients' distrust in nurses' competency, interference from patients' relations, inadequate knowledge, patient's dissatisfaction with output, patients' emotional fluctuations. Health environment–related barriers also include excessive workload, unconducive environment, and environmental changes. Given the relevance of therapeutic communication to health service, the study, among other things recommends that efforts be exerted by sector actors to address the challenges and help promote quality in health-care service and delivery.